2020
DOI: 10.16919/bozoktip.599884
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Burnout Syndrome Among Intensive Care Unit Professionals

Abstract: Amaç: Tükenmişlik sendromu (BS), yaygın olarak insanların yüz yüze çalıştığı mesleklerde bireylerin, duygusal yönden kendilerini tükenmiş hissetmeleri, işleri gereği karşılaştıkları insanlara karşı duyarsızlaşmaları ve kişisel başarı duygularında azalma şeklinde görülen bir sendromdur. Tükenmişlik sendromu; duygusal tükenme (EE), duyarsızlaşma (DEP) ve azalmış kişisel başarı (PA) ile karakterizedir. Maslach Tükenmişlik Envanteri (MBI) bu üç boyutu ayrı ayrı belirlemek için 22 sorudan oluşan bir ankettir. Bu ça… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The fact that nurses in Turkey experience various problems such as lack of autonomy in occupational and personal rights, low income, long working hours, and corrupt professional relationships that need to be resolved (Terzi et al, 2019) might explain their high burnout levels. In a study examining the factors related to burnout syndrome among ICU personnel in Turkey, the researchers showed that 68.7% had high levels of emotional exhaustion, and 38.3% experienced high levels of depersonalization (Doğan et al, 2020). The findings of other studies conducted in Turkey (Özsoylu et al, 2017; Terzi et al, 2019) and other countries (Filho et al, 2019; Jarden et al, 2020; Mealer, 2016; Ntantana et al, 2017; Torre et al, 2019; Vasconcelos et al, 2018) have demonstrated that ICU nurses experienced significant levels of depersonalization and emotional exhaustion, thus, supporting the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that nurses in Turkey experience various problems such as lack of autonomy in occupational and personal rights, low income, long working hours, and corrupt professional relationships that need to be resolved (Terzi et al, 2019) might explain their high burnout levels. In a study examining the factors related to burnout syndrome among ICU personnel in Turkey, the researchers showed that 68.7% had high levels of emotional exhaustion, and 38.3% experienced high levels of depersonalization (Doğan et al, 2020). The findings of other studies conducted in Turkey (Özsoylu et al, 2017; Terzi et al, 2019) and other countries (Filho et al, 2019; Jarden et al, 2020; Mealer, 2016; Ntantana et al, 2017; Torre et al, 2019; Vasconcelos et al, 2018) have demonstrated that ICU nurses experienced significant levels of depersonalization and emotional exhaustion, thus, supporting the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The literature presents low rates of personal accomplishment, which is another component of burnout, in ICU nurses (Filho et al, 2019; Jarden et al, 2020; Mealer, 2016; Ntantana et al, 2017; Torre et al, 2019; Vasconcelos et al, 2018). For example, a study conducted with personnel who worked at ICUs found that 67.2% of the participants had low personal accomplishment levels (Doğan et al, 2020). This study indicated that 67.1% of the ICU nurses had low levels of personal accomplishment.…”
Section: Discussionmentioning
confidence: 99%